Analisis Sosiologi Pendidikan terhadap Integrasi Nilai-Nilai Islam dalam Sistem Pendidikan Modern - Dyah Pranowo Lestari; Tutuk Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Educational modernization brings significant changes to learning patterns, social relationships, and the value orientations of students. These changes offer opportunities in the form of expanded learning access and technological innovation, yet they also present challenges such as weakened morality, increasing individualism, and shifts in school culture. This study aims to analyze how Islamic values can be integrated into the process of educational modernization from the perspective of the sociology of education. Using a descriptive qualitative approach based on library research, the study draws primarily on theories of educational sociology and Islamic education literature. The findings indicate that the values of tawhid, ‘adl, ukhuwah, and akhlaq al-karimah function as an ethical framework capable of guiding modernization to remain oriented toward character development, spirituality, and social responsibility. The integration of these values is further strengthened through collaboration among schools, families, and communities. These findings highlight the need to reinforce moral values in the transformation of education in the modern era.